Human noroviruses' fondness for histo-blood group antigens - Singh, Bishal; Leuthold, Mila; Hansman, Grant S. (Journal of virology, 2015)
Human noroviruses are the dominant cause of outbreaks of gastroenteritis around the world. Human noroviruses interact with the polymorphic human histo-blood group antigens (HBGAs), and this interaction is thought to be important for infection. Indeed, synthetic HBGAs or HBGA-expressing enteric bacteria were shown to enhance norovirus infection in B cells. A number of studies have found a possible relationship between HBGA type and norovirus susceptibility. The genogroup II, genotype 4 (GII.4) noroviruses are the dominant cluster, evolve every other year, and are thought to modify their binding interactions with different HBGA types. Here we show high-resolution X-ray crystal structures of the capsid protruding (P) domains from epidemic GII.4 variants from 2004, 2006, and 2012, cocrystallized with a panel of HBGA types (H type 2, Lewis Y, Lewis B, Lewis A, Lewis X, A type, and B type). Many of the HBGA binding interactions were found to be complex, involving capsid loop movements, alternative HBGA conformations, and HBGA rotations. We showed that a loop (residues 391 to 395) was elegantly repositioned to allow for Lewis Y binding. This loop was also slightly shifted to provide direct hydrogen- and water-mediated bonds with Lewis B. We considered that the flexible loop modulated Lewis HBGA binding. The GII.4 noroviruses have dominated outbreaks over the past decade, which may be explained by their exquisite HBGA binding mechanisms, their fondness for Lewis HBGAs, and their temporal amino acid modifications. - IMPORTANCE Our data provide a comprehensive picture of GII.4 P domain and HBGA binding interactions. The exceptionally high resolutions of our X-ray crystal structures allowed us to accurately recognize novel GII.4 P domain interactions with numerous HBGA types. We showed that the GII.4 P domain-HBGA interactions involved complex binding mechanisms that were not previously observed in norovirus structural studies. Many of the GII.4 P domain-HBGA interactions we identified were negative in earlier enzyme-linked immunosorbent assay (ELISA)-based studies. Altogether, our data show that the GII.4 norovirus P domains can accommodate numerous HBGA types.